Constructing Political Image Through Suara Merdeka Newspaper During The 2004 Election In Semarang - Cindi Rahmawati Dewi; Putri Agus Wijayati (Universitas Islam Negeri Sumatera Utara, 2026)
This study examines how the political images of the presidential and vice-presidential candidates were shaped during the first round of the 2004 presidential election, as reflected in the coverage of the Suara Merdeka newspaper in Semarang City. The 2004 election marked an important stage in the development of Indonesian democracy, as it was the first time the president and vice-president were chosen directly by the public. As a result, newspapers became a key tool for political communication. The main source of information for this study is the Suara Merdeka newspaper during the 2004 election campaign, supported by references from books and academic articles. The research reveals that Suara Merdeka did more than just report news—it actively influenced the public perception of the candidates by selecting specific issues, determining how often they were covered, and highlighting certain symbols. Therefore, newspapers played an important role in shaping how the public understood the political competition during this period of democratic change.